CARACTERIZAÇÃO MORFOLÓGICA E PATOGÊNICA DE ISOLADOS DE Sclerotinia sclerotiorum (Lib.) de Bary E DETECÇÃO EM SEMENTES DE SOJA - Grabicoski, Edilaine Mauricia Gelinski (2012)
The white mold disease, caused by the fungus Sclerotinia sclerotiorum (Lib.) de Bary, responsible for large losses in soybean (Glycine max (L.) Merrill). The pathogen has more than 400 hosts and presents the formation of a resistance structure (sclerotia), difficulting the disease control, thus increasing the importance of the pathogen in Brazilian agriculture. The seeds are the main spreading disease means, a quickly and correct presence detection of the pathogen is important to control the white mold, especially for non-infested areas by the pathogen. In this study, 57 S. sclerotiorum isolates were morphological and pathologically characterized to assess variations within the specie. Also was developed a method to detect the pathogen directly from seed-soak liquor of infected soybean seeds, through PCR. The proposed method was compared to the traditional recommended methods. The pathogen isolates showed some morphological variations among themselves, as the number and weight of the formed sclerotia. Pathologically, were observed two and seven pathogenic levels second, respectively, the soybean inoculation on the stem and on the detached trifoliate leaves. By the detection method, it was possible to detect one seed artificially contaminated in the sample with 400 total seeds. In naturally contaminated seeds, was possible to detected the pathogen presence in a sample that, according to the method of incubation on paper roll and on Neon-S medium, respectively, presented 1 and 3 seeds contaminated in four hundred seeds. The proposed methodology is promising for the detection of S. sclerotiorum, however, requires optimization because many false negative results were obtained, mainly due to substances released by the seeds that inhibited the PCR reaction. The use of filter in the samples has presented as a possible tool to overcome the PCR inhibitors. For the optimization of the method, increase the size of seed samples, use of filters, others techniques such as nested PCR, Real-Time PCR and DNA probes can help overcome these difficulties.